Indonesia's Strategy in Infrastructure Development Maritime Through China's Belt and Road Initiative (BRI) - Midiyani, Nina; Yumitro, Gonda (Journal of Sustainable Construction, 2026)
The improvement of global well-being and economic progress is largely driven by the development of infrastructure. An increasing number of countries, including Indonesia, recognize that investing in physical infrastructure is essential to achieving national development objectives within the global context. This article centers on Indonesia’s involvement in developing maritime infrastructure within the framework of China’s Belt and Road Initiative (BRI) and aims to analyse the strategies and efforts undertaken by states in advancing global infrastructure. This research looks at how Indonesia is improving its marine infrastructure development by taking use of its partnership with China via the BRI. To decipher the partnership's underlying political, economic, and strategic dynamics, this study technique employs literature and policy analysis. Analysis shows that Indonesia is strategically using the BRI to speed up the development of its marine infrastructure, regional connectivity, and international collaboration.